Birth weight and childhood leukemia: A meta‐analysis and review of the current evidence - Caughey, Robert W.; Michels, Karin B. (International journal of cancer, 2009)
A growing body of evidence suggests that childhood leukemia may be initiated in utero when lymphoid and myeloid cells are not fully differentiated and are particularly susceptible to malignant transformation. A fixed effects meta‐analysis examining the association between birth weight and childhood leukemia was conducted including 32 studies and 16,501 cases of all types of leukemia (OL), 10,974 cases of acute lymphoblastic leukemia (ALL), and 1,832 cases of acute myeloid leukemia (AML). The odd ratios (OR) for the association of high birth weight with OL, ALL and AML were 1.35 (95% CI: 1.24, 1.48), 1.23 (95% CI: 1.15, 1.32), and 1.40 (95% CI: 1.11, 1.76), respectively, compared with normal birth weight. Low birth weight was not associated with overall and ALL leukemia, but with AML (OR = 1.50; 95% CI: 1.05, 2.13). Per 1000 g increase in birth weight, the OR for OL was 1.18 (95% CI: 1.13, 1.23) and ALL 1.18 (95% CI: 1.12, 1.23). The combined available evidence from observational studies suggests that high birth weight is associated with an increased risk of overall leukemia and ALL. For AML the risk may be elevated at both high and low extremes of birth weight, suggesting a U‐shaped association. © 2008 Wiley‐Liss, Inc.